The treatment practices for anterior urethral strictures in China: A case-based survey - Hou, Changhao; Lin, Jiahao; Gu, Yubo; Yuan, Wei; Wang, Zeyu; Xiu, Xianjie; Fu, Qiang; Song, Lujie (Frontiers in Surgery, 2022)
Objective: To investigate the treatment concept of Chinese urologists for anterior urethral strictures based on actual cases. Methods: A self-designed case-based questionnaire was distributed to the members of Official WeChat account of Learning Union from March 19, 2020, to April 10, 2020. Questionnaires requested respondents’ demographic information and responses to five cases of anterior urethral stricture: short obliterative bulbar urethral stricture caused by straddle injury (Case 1), idiopathic bulbar urethral stricture after failure of multiple endoscopic therapy (Case 2), iatrogenic long penile urethral stricture (Case 3), lichen sclerosis-related urethral stricture (Case 4), and anterior urethral stricture in indwelling catheter after multiple failure of endoscopic surgery (Case 5). Data was described by frequency and percentage. Results: A total of 1267 valid anonymous questionnaires were received. Urethroplasty was recommended more frequently than endoscopic surgery (Case 1: 36.2% VS 26.7%; Case 2: 42.8% VS 33.6%; Case 3: 50.7% VS 31.5%). Referrals patients to other urologists engaged in urethral repair and reconstruction account for a high portion of the treatment (Case 1: 18%; Case 2: 23%, Case 3: 36.2%, Case 4: 15%, Case 5: 9%). Excision and primary anastomosis urethroplasty (EPA) was preferred for treatment of Case 1 (42.5%). For Case 2, the most popular choice was EPA (30.6%). Although the patient has a history of failure in endoscopic surgery, 21.7% of urologists continue to choose endoscopic surgery. For Case 3, 20.0% of urologists would perform oral mucosal urethroplasty. Surprisingly, 5.9% chose EPA. For Case 4, 37.3% of urologists selected meatotomy, 30.4% suggested that glans and urethral biopsies should be performed. 21.0% chose to use steroid ointment after surgery. For Case 5, 26.3% of the respondents believed that urethrography should be performed after removing catheter more than one week, if the urine is obstructed during the period, performing cystostomy firstly. Conclusions: In China, the concept of urethroplasty is more widely accepted than endoscopic surgery for the treatment of anterior urethral strictures. The concept of referral has been widely formed among Chinese urologists. Better understanding of the comprehensive treatment of lichen sclerosis related anterior urethral stricture and the principle of urethral rest should be strengthened.